Foliar Fatty Acids and Sterols of Soybean Field Fumigated with SO(2) - Grunwald, Claus (1981)
Sixty-day-old soybean plants were exposed in the field to 78.7 parts per one-hundred million of SO(2) in an open-air fumigation system for 20 days. Leaves from the top one-fourth and bottom one-fourth of the plants were analyzed for chlorophyll, free fatty acids, fatty acid esters, polar lipid fatty acids, and sterols. Fumigated plants had a lower chlorophyll, free fatty acid, and polar lipid content, but a higher fatty acid ester content. Of the individual fatty acids, linoleic and linolenic acid increased with SO(2) fumigation while palmitic acid decreased. SO(2) fumigations had only a minor effect on leaf sterols. In general, the lower, more mature leaves showed a greater response to SO(2) exposure.